A new species of smooth horned frog, genus Proceratophrys Miranda-Ribeiro (Amphibia: Anura: Cycloramphidae), from the Atlantic Rainforest of eastern Bahia, Brazil - Cruz, Carlos Alberto Gonçalves; Napoli, Marcelo Felgueiras (Zootaxa, 2010)
We describe a new species of smooth horned frog related to the Proceratophrys appendiculata complex, constituting the northernmost record of that complex for the Atlantic Forest remnants in eastern Bahia, northeastern Brazil, within a region known as Vale do Jiquiriçá. Proceratophrys sanctaritae sp. nov. is diagnosed from all congeners by the combination of medium size (snout–vent length 38.4–45.5 mm), single and long uni-cuspidate palpebral appendage, rostral appendage longer than upper lip width, presence of preocular crest, frontoparietal crest poorly developed, color of ventral surfaces, and acoustic parameters of the advertisement call.